Mesophilic anaerobic digestion monitoring using a headspace Carbon Dioxide method - Greggio, Ellen (Cranfield University, 2010)
Anaerobic digesters are often not operated to full capacity and are recurrently subjected to adverse operational practices due to: temperature fluctuations, inconstant feeding regimes, variable solids content on the feed, changes in loading rates etc. The use of standard online monitoring indicators (pH, alkalinity, gas production and compositions)is insufficient to detect the perturbation at an early stage as these parameters are linked to the final product of the process, causing delays when diagnosing digester imbalances. On the other hand, volatile fatty acids (VFA) have been widely recognized as a key parameter for understanding and controlling anaerobic processes as they are intermediate products and real time indicators of the digester stability. Application of on-line instrumentation for VFA measurement has been limited as all developed instrumentations are based on expensive equipments (Gas Chromatograpy, High Performance Liquid Chromatography, Fourier Transform Infra-Red spectrometer etc.) and require. sample preparations involving the use of filtration, membranes, chemical additions, therefore triggering extensive maintenance. Cont/d.